Pembinaan Santri Pondok Pesantren NW Kayangan Lombok Barat dalam Pembuatan Produk Olahan Jamur Tiram Berbasis Entrepreneurship - Efendi, Ismail; Dewi, Ika Nurani; Utami, Septiana Dwi; Harisanti, Baiq Muli; Primawati, Sri Nopita (Jurnal Pengabdian UNDIKMA, 2020)
Oyster mushrooms have high economic potential because they can be processed into a variety of foods and snacks, as well as prospects for development in the community. One of the potentials that can be used by the hut to hone students’ life skills is by providing training for the manufacture of oyster mushroom products. The purpose of these community service activities is to be expected later when students graduating from the NW Kayangan Islamic Boarding School can become young entrepreneurs who make them economically independent and can open new jobs for the people in their respective homes. Community service activities focus on training in processing oyster mushrooms into products in the form of nutritious satay and crispy mushrooms that are nutritious and of high economic value, targeting the students and teachers at Pondok NW Kayangan, West Lombok Regency. The activity method includes: (1) preparation phase, (2) counseling, and (3) demonstration and training on making oyster mushroom and crispy mushroom. This activity increases the knowledge and skills of students in processing oyster mushroom raw materials. This is evidenced by the results of processed oyster mushrooms in the form of mushroom satay and krispi mushroom created by teachers and students.